A miniaturized silicon-based ground ring guarded patch resonator and filter - Ma, Kaixue (2009)
A new miniaturized ground ring guided microstrip patch filter developed on the silicon wafer using micromachined technology is reported. The ground shunt can be used to lower the operating frequency up to one-third as compared to the traditional patch resonator. The size of the designed band pass filter operating in 5.17 GHz is only 8.7 mm×2.9 mm.